2012
DOI: 10.1161/atvbaha.111.236877
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Assessed Physical Activity, Sedentary Time, and Coronary Artery Calcification in Healthy Older Adults

Abstract: Objective-Physical activity is related to lower risk of cardiovascular disease, but data relating to coronary lesions have been conflicting. These inconsistencies may in part be due to unreliable assessment of physical activity and limitations imposed by self-reported data. The purpose of this study was to determine the relationship between objectively measured physical activity and coronary artery calcium (CAC). Methods and Results-Participants were 443 healthy men and women (mean ageϭ66Ϯ6 years), without his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 43 publications
1
48
2
6
Order By: Relevance
“…(2012) showed that 54.4% of healthy adults with a mean age of 66 (±6) years was at least 30 minutes/day physically active at moderate intensity, 36 compared to 56% of the HF patients in the present study. The time that stable outpatients with HF spent on activities at moderate intensity is also comparable with patients with congenital heart disease (54 ± SD 55 versus 59± SD 40 min/day respectively).…”
Section: Related Factors Of Daily Physical Activity (Steps/day)mentioning
confidence: 39%
“…(2012) showed that 54.4% of healthy adults with a mean age of 66 (±6) years was at least 30 minutes/day physically active at moderate intensity, 36 compared to 56% of the HF patients in the present study. The time that stable outpatients with HF spent on activities at moderate intensity is also comparable with patients with congenital heart disease (54 ± SD 55 versus 59± SD 40 min/day respectively).…”
Section: Related Factors Of Daily Physical Activity (Steps/day)mentioning
confidence: 39%
“…In addition, it has been shown that a slow habitual walking pace is negatively associated with coronary artery calcium [16], whereas this association was not observed in older individuals [17]. Because poor gait ability and physical activity levels are hallmarks of frailty syndrome, it would be interesting to investigate the calcium score in frail individuals, comparing its values with robust oldest old.…”
Section: Introductionmentioning
confidence: 99%
“…VPA group was statistically younger than MPA group, and the impact of age in the accomplishment of higher levels of physical activity intensity by younger women was of 18%. It is common to find differences between younger and older groups of age with respect to either intensity or quantity of daily physical activity results (26)(27)(28), independently of the cut-point used. Other studies also reveal negative correlations between age and minutes of physical activity (12).…”
Section: Discussionmentioning
confidence: 99%